PENGARUH VARIASI PENDINGINAN DAN HOLDING TIME TERHADAP NILAI KEKERASAN DAN STRUKTUR MIKRO PADA PERLAKUAN PANAS BAJA ASSAB 88 - syarief, akhmad (TURBO [Tulisan Riset Berbasis Online], 2024)
Along with the rapid development of science, improving material properties needs to be done to support the needs in the industrial world. This study aims to determine the effect of heat treatment with variations in cooling media and holding time on the value of hardness and microstructure in heat treatment of Assab 88 steel. The research process begins with cutting Assab 88 steel, then the heating process is carried out with a temperature of 850˚C, then the cooling process is carried out with various media such as air, water and oil with holding time variations for 30 minutes, 45 minutes and 60 minutes. The results showed that the highest hardness value was found in water cooling media with a holding time of 60 minutes at 87.1 HRB and the lowest value in air cooling media at 78.1 HRB. Microstructure testing in water cooling media will form martensite which makes the steel harder but brittle, while with oil cooling media will produce a balance between hardness and toughness because bainite structures are formed and martensite is more dominant and a little pearlite. Keywords: Cooling medium, holding time, hardness test, microstructure test, ASSAB 88 steel.